The brush as a dagger. The dialectical structure of Titian’s painting as wound and refuge (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
This article shows that Titian's painting contains at its core a dialectical scheme of tension between opposing elements: jovial/tragic, classical/christian, dagger/refuge. This tension feeds the intersection of meaningful structures that characterize every work of art. This dialectic explains the ultimate meaning of painting for Titian. We focus this dialectic on the work The Flaying of Marsyas, a work that teaches that painting, art in general, for Titian opens wounds, it is a dagger, but it is also a shelter in which to take refuge from the horror of the world.
Keywords: Titian; painting; Marsyas; dialectic; wound; refuge